PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DAN KOMUNIKASI MATEMATIKA SISWA PADA MATERI HIMPUNAN DI KELAS VII SMP NEGERI 5 BATANG ANGKOLA TAHUN AJARAN 2021-2022 - Nova Christina Dewi; Puspa Riani Nasution; Siti Gabena Hasibuan (JURNAL MathEdu (Mathematic Education Journal), 2022)
This study aims to determine whether the application of a Think Pair Share (TPS) cooperative learning model is better than using a direct learning model on the linear inequality of one variable material on the communication skills of class VII students of SMP Negeri 5 Batang Angkola T.A. 2021-2022. The population in this study were all students of SMP Negeri 5 Batang Angkola T.A 2021-2022. The sample in this study consisted of 2 classes, namely class VII-1 and class VII-2. This type of research is a quasi-experimental. In this study, the data collection tool used was a test instrument in the form of a description, each test consisting of 3 questions that had been declared valid by a team of experts and based on trials on non-sample research. From the results of the post-test data analysis of mathematical communication skills using the t-test level = 0.05, it was obtained ttable = 1.9973 and tcount = 3.389. So, it was concluded that there was an effect of the Think Pair Share (TPS) cooperative learning model on communication. students' mathematics on the material of one variable linear inequalities class VII SMP Negeri 5 Batang Angkola T.A. 2021-2022. The suggestion that researchers can give is that the Think Pair Share (TPS) cooperative learning model is suitable for use as a teaching method with efficient use of time and is suitable for linear inequalities of one variable.